2022
DOI: 10.1108/jrme-08-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

Measuring factors influencing entrepreneurial intention across gender in India: evidence from Global Entrepreneurship Monitor (GEM) Database

Abstract: Purpose This paper aims at measuring the factors such as cognitive, economic and social recognition affecting entrepreneurial intention across gender in India. Design/methodology/approach This study is based on the Adult Population Survey of Global Entrepreneurship Monitor covering 4,000 respondents on their characteristics, perception and attitude toward entrepreneurship and intention of individuals for starting businesses. The data has been analyzed using chi-square statistics and logistics regression. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…The most prevalent method is a single-dimensional tool with a dichotomous question (also known as a closed dummy question) that asks participants whether they would give up entrepreneurial activities due to fear of failure. The question was adapted from the Global Entrepreneurship Monitor (GEM), a global project investigating the degree of EFoF in different countries and regions, by asking the following question: “Would fear of failure prevent you from starting a business?” [ 41 ]. Although many EFoF studies have adopted this single-question measurement [ [42] , [43] , [44] ], researchers have criticized its simplicity and neglect of the multidimensional essence of EFoF [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent method is a single-dimensional tool with a dichotomous question (also known as a closed dummy question) that asks participants whether they would give up entrepreneurial activities due to fear of failure. The question was adapted from the Global Entrepreneurship Monitor (GEM), a global project investigating the degree of EFoF in different countries and regions, by asking the following question: “Would fear of failure prevent you from starting a business?” [ 41 ]. Although many EFoF studies have adopted this single-question measurement [ [42] , [43] , [44] ], researchers have criticized its simplicity and neglect of the multidimensional essence of EFoF [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gender. Gender has been the focus of many studies on EFoF, revealing notable variations across contexts and populations, including college students [ 41 , [93] , [94] , [95] , [96] ]. The prevailing view suggests that women tend to perceive higher EFoF levels than males.…”
Section: Discussionmentioning
confidence: 99%
“…Education, gender, diversity education, and owner's minority status have significant impacts on digital innovation [43]. Attitude is a strong predictor of decision making among Italian university students [44], and there are differences between men and women in their perceptions of cognitive, economic, and social recognition [45]. Perceived self-efficacy and perceived desirability are significant factors that enable EI among business students in Pakistani universities, and entrepreneurial knowledge moderates these associations [46].…”
Section: Entrepreneurial Intention (Ei)mentioning
confidence: 99%
“…The authors noted that the lack of any elements thought to be predictors of entrepreneurial intention is not the reason for this lower female entrepreneurial activity, but rather that it is connected to the existence of implicit obstacles for women that affect their entrepreneurial intention. Most recently, characteristics affecting entrepreneurial ambition across gender were measured by Ali et al (2023). The study revealed that a number of factors, including cognitive (self-efficacy, knowledge of entrepreneurs, and fear of failure), economic (perceived opportunity, career choice, and ease of starting), and social recognition (sense of equality, status and respect in society, and social welfare), significantly affect both men and women's likelihood of becoming entrepreneurs, with the effects of age, family size, education, working status, and household size being controlled.…”
Section: Dominant Factors Of Entrepreneurial Intentionmentioning
confidence: 99%